Αiρεσισ and αiρετικoσ in the Alexandrine school of the II and III centuries (Clement of Alexandria and Origen) - di Paolo, Maria Laura; Limone, Vito (Vox Patrum, 2018)
The aim of this study is to outline the use of the terms airesis and airetikos according the two main representatives of the Alexandrine School, Clement and Origen. In the Stromateis the word airesis has many meanings and, first of all, it is related to “the act of choice”, then, it is also a synonym for a “school” or a “sect”, hence it signifies Christian “heresy”. The connection between human freedom and schools, mainly philosophical ones, but also the schools of medicine, points out that Clement conceives “heresy” as an error, an incorrect way of thinking due to a wrong, even malicious choice, often of an intellectual nature; it suggests conscious deformation of a message. Hence, Clement contrasts the Gnostic airetikos and the “true Gnostic”, the man of faith who by studying the biblical texts and the Greek disciplines is enlightened by Christ (Stromata VII 92, 7). About the Origen’s usage of the term a†resij in his Contra Celsum it is worth to note that, firstly, the word a†resij always indicates the philosophical schools of Late Antiquity (cf. Contra Celsum 4, 45; 8, 53); secondly, that Origen aims at persuading his enemy, Celsus, that Christian religion is neither a refusal of philosophical schools nor something very different from them, but it may be regarded as an a†resij too and, in order to argue this, he shows that not only Christian religion and philosophical schools share some moral and cosmological topics (Contra Celsum 3, 66; 3, 80), but also that both Christians and philosophers are moved by the some ¥logoj for£ (Contra Celsum 1, 10). Therefore, in Origen’s Contra Celsum the a†resij means not only the philosophical schools of the II and III centuries, but also the Christian religion as long as it is accepted by the Heathens. In conclusion, this study shows, once again, that, as the two representatives of Alexandria were in dialogue with the brilliant exponents of the contemporary philosophy, they were called to explain the importance of faith on the intellectual side, using some terms and conceptions of the main schools, on the one side, and by distinguishing Christian faith from them, on the other.